The Scholarly Study of Abeghyan’s linguistic Heritage - Sukiasyan, Henrietta (Bulletin of Yerevan University B: Philology, 2026)
Manuk Abeghyan is one of the most prominent figures in Armenian linguistic scholarship, whose multifaceted work played a decisive role in shaping the theoretical and practical foundations of the modern Eastern Armenian literary language. His studies in phonetics, morphology, semantics, and syntax laid the groundwork for a new stage in the scientific examination of Armenian. Abeghyan’s major works—The Theory of the Armenian Language, Grammar of Ashkharhabar, and Syntax of Ashkharhabar—became classics of Armenology, freeing the linguistic description of Eastern Armenian from Classical Armenian models and affirming its structural independence. His contributions to lexicography, including the creation of military and medical dictionaries, opened a new chapter in Armenian dictionary-making. Abeghyan’s principles of orthographic reform, despite the controversies of the time, remained scientifically justified. His linguistic legacy continues to serve as an inexhaustible source for future scholars and stands as one of the foundational pillars of Armenian linguistic studies.
Keywords: Manuk Abeghyan; linguistics; heritage; world dialect; syntax; lexicography; grammar; phonology